Insight Into the Molecular Mechanisms Underpinning the Mycoremediation of Multiple Metals by Proteomic Technique - Dey, Priyadarshini; Malik, Anushree; Singh, Dileep Kumar; Haange, Sven-Bastiaan; von Bergen, Martin; Jehmlich, Nico (Frontiers in Microbiology, 2022)
We investigated the fungus Aspergillus fumigatus PD-18 responses when subjected to the multimetal combination (Total Cr, Cd2+, Cu2+, Ni2+, Pb2+and Zn2+) in synthetic composite media. To understand how multimetal stress impacts fungal cells at molecular level, the cellular response of A.fumigatus PD-18 to 30 mg/L multimetal stress (5 mg/L of each individual heavy metal) were determined by proteomics. The comparative fungal proteomics displayed the remarkable inherent intracellular and extracellular mechanism of metal resistance and tolerance potential of A.fumigatus PD-18.This study reported 2238 proteins of which 434 proteins were exclusively expressed in multimetal extracts. The most predominant functional class expressed was for cellular process and signalling. The type of proteins and the number of proteins that were up-regulated due to various stress tolerance mechanisms were posttranslational modification, protein turnover and chaperones (42); translation, ribosomal structure and biogenesis (60); intracellular trafficking and secretion and vesicular transport (18). Additionally, free radical scavenging antioxidant proteins such as superoxide dismutase was upregulated upto 3.45-fold, transporters systems such as protein transport (SEC31) upto 3.31-fold to combat the oxidative stress caused by the multiple metals. Also, protein–protein interaction network analysis revealed that cytochrome c oxidase and 60S ribosomal protein played key roles to detoxify the multimetals. To the best of our knowledge, this study of A.fumigatus PD-18 provide valuable insights towards the growing research in comprehending the metal microbe interactions in the presence of multimetals. This will facilitate in developing novel molecular markers for contaminant bioremediation.